2018
DOI: 10.19111/bulletinofmre.501432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Alternatives for Gold Ore Grinding Circuits by Using of Laboratory Studies Results and Simulation Method; Case Study: Iranian Gold Co.

Abstract: In this study, simulation aided design of grinding circuit for a gold mine in Iran is presented. The main parameters for the design of the grinding circuit are the ore specifi cations and the considered operating conditions. Ore specifi cations were characterized by grinding tests, which included the Drop-weigh test (A, b), the abrasion test (t a) and the Bond Work Index test (W i). For this study, the operating conditions for the processing plant are the ability to process clayey minerals and the plant throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…As a result, various types of research have reported different results and interpretations for similar grinding aids. Therefore, the diversity of the materials used and their different effects have hindered the development of a comprehensive understanding and approach (Sverak et al, 2013;Hosseinzadeh Gharehgheshlagh et al, 2021). In general, the impact of grinding aids on the cement industry can be summarized as follows: i) Reducing van der Waals forces due to the addition of grinding aids increases the fluidity of solids, which also directly affects the retention time of materials inside the mill (Mardulier, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, various types of research have reported different results and interpretations for similar grinding aids. Therefore, the diversity of the materials used and their different effects have hindered the development of a comprehensive understanding and approach (Sverak et al, 2013;Hosseinzadeh Gharehgheshlagh et al, 2021). In general, the impact of grinding aids on the cement industry can be summarized as follows: i) Reducing van der Waals forces due to the addition of grinding aids increases the fluidity of solids, which also directly affects the retention time of materials inside the mill (Mardulier, 1961).…”
Section: Introductionmentioning
confidence: 99%